1994
DOI: 10.1002/pola.1994.080321216
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolyzable poly(ester‐urethane) networks from L‐lysine diisocyanate and D,L‐lactide/ϵ‐caprolactone homo‐ and copolyester triols

Abstract: SYNOPSISBioabsorbable poly (ester-urethane) networks were synthesized from ethyl 2,6-diisocyanatohexanoate (L-lysine diisocyanate) (LDI) and a series of polyester triols. LDI was synthesized by refluxing L-lysine monohydrochloride with ethanol to form the ester, which was subsequently refluxed with 1,1,1,3,3,3-hexamethyldisilazane to yield a silazane-protected intermediate. This product was then phosgenated using triphosgene. Polyester triols were synthesized from D,L-lactide, c-caprolactone, or comonomer mixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
109
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(111 citation statements)
references
References 14 publications
2
109
0
Order By: Relevance
“…While the first curing agent is a cyclic trifunctional isocyanate, the latter is an aliphatic difunctional isocyanate. Although the synthetic route for the preparation of the isocyanate functionality still requires a petroleum-based compound, namely phosgene, 36 the carbon mass of the L-lysine amino acid-based EELDI is 75% renewable, which combined with fully bio-based polyesters provides cured coatings with a large renewable content.…”
Section: Thermal Properties Of Sugar-based Polyestersmentioning
confidence: 99%
“…While the first curing agent is a cyclic trifunctional isocyanate, the latter is an aliphatic difunctional isocyanate. Although the synthetic route for the preparation of the isocyanate functionality still requires a petroleum-based compound, namely phosgene, 36 the carbon mass of the L-lysine amino acid-based EELDI is 75% renewable, which combined with fully bio-based polyesters provides cured coatings with a large renewable content.…”
Section: Thermal Properties Of Sugar-based Polyestersmentioning
confidence: 99%
“…EELDI and DDI have been selected to study their applicability as renewable diisocyanates in PU synthesis. DDI is a vegetable oil-based product from BASF while EELDI is derived from the amino acid lysine [43]. The best conditions to prepare a good coating and the corresponding curing procedure were evaluated.…”
Section: Curing and Coating Evaluation Of Sorbitol-based Polyestersmentioning
confidence: 99%
“…Recently, network polymers derived from terminal functionalized star-shaped biodegradable polyesters have gathered considerable attention since the curing reaction of their at least three functional groups easily generates crosslinked structures and the crosslinking density can be controlled by changing the arm length [3,13,[29][30][31][32][33][34][35][36][37][38]. For example, Storey et al reported the networks prepared by the crosslinking reaction of hydroxy-terminated 3-armed random copolymers of D,L-LA and CL with L-lysine diisocyanate [30]. Amsden et al reported biodegradable elastomeric networks prepared by the photo-crosslinking reaction of acrylate-terminated GC-based 3-armed random copolymers of LA and CL [31].…”
Section: Introductionmentioning
confidence: 99%
“…Jahandideh et al reported the thermomechanical properties of cured products of methacrylate-functionalized star-shaped lactide oligomers with a XL core and their biocomposites with jute fibers [36]. Also, we reported pentaerythritol-based polymer networks (PEPN-4scLAO/2CLOs) prepared by reactions of methylenediphenyl 4,4′-diisocyanate (MDI), hydroxy-terminated two enantiomeric 4-armed star-shaped lactide oligomers bearing a pentaerythritol core (PE4LLAO and PE4DLAO) and a diethylene glycol-based hydroxy-terminated 2-armed ε-caprolactone oligomer (H2CLO) [37], and glycerol (GC)-based polymer networks (GCPN-3scLAO/2CLOs) by reactions of hexamethylene diisocyanate (HDI), hydroxy-terminated Recently, network polymers derived from terminal functionalized star-shaped biodegradable polyesters have gathered considerable attention since the curing reaction of their at least three functional groups easily generates crosslinked structures and the crosslinking density can be controlled by changing the arm length [3,13,[29][30][31][32][33][34][35][36][37][38]. For example, Storey et al reported the networks prepared by the crosslinking reaction of hydroxy-terminated 3-armed random copolymers of D,L-LA and CL with L-lysine diisocyanate [30].…”
Section: Introductionmentioning
confidence: 99%